The contribution of methamphetamine use to crime: Evidence from Australian longitudinal data. (1st November 2020) - McKetin, Rebecca; Boden, Joseph M.; Foulds, James A.; Najman, Jake M.; Ali, Robert; Degenhardt, Louisa; Baker, Amanda L.; Ross, Joanne; Farrell, Michael; Weatherburn, Don
Highlights: There was a five-fold increase in crime during periods of methamphetamine use amongst people who used the drug. This increase in criminal involvement was beyond pre-existing risk for criminality. These associations were not accounted for by polysubstance use or socioeconomic disadvantage. Abstract: Background: To quantify the extent to which methamphetamine use is associated with increases in crime net of any premorbid risk of criminality among people who use the drug. Methods: Four one-month data panels from 469 participants dependent on methamphetamine were drawn from the MATES cohort (N = 501). Odds ratios for within-person effects were extracted from a random intercept logistic regression model for crime during periods of methamphetamine use compared to no use. Effects were adjusted for time-varying measures of age, other substance use, and socio-economic disadvantage (income, unemployment and unstable accommodation). Involvement in crime (property crime, drug dealing, fraud, violent crime) and days of methamphetamine in the past month were assessed using the Opiate Treatment Index. Results: Crime was more likely during months when participants used methamphetamine compared to when they did not (OR 13.2 95% CI 8.5–20.6; AOR 4.7 95% CI 2.8–8.0), this reflecting more property crime (OR 10.6 95% CI 6.3–18.0; AOR 5.5 95% CI 2.8–10.8), violent crime (OR 8.2 95% CI 4.2–15.9; AOR 3.4 95% CI 1.5–8.0), fraud (OR 3.4, 95% CI 2.0–5.8; AOR 1.7 95% CI 0.8–3.3) and dealing drugs (OR 18.2 95% CI 10.2–32.5; AOR 5.9 95% CI 3.0–11.9), although the adjusted relationship for fraud was not significant. Effects were dose related. Conclusions: The use of methamphetamine was associated with significant increases in crime beyond premorbid risk for criminality. Crime is a likely social consequence of methamphetamine use and efforts are needed to reduce this impact.